Singularly perturbed telegraph equations with applications in the random walk theory. (1998) - Banasiak, Jacek; Mika, Janusz R.
Abstract : In the paper we analyze singularly perturbed telegraph systems applying the newly developed compressed asymptotic method and show that the diffusion equation is an asymptotic limit of singularly perturbed telegraph system of equations. The results are applied to the random walk theory for which the relationship between correlated and uncorrelated random walks is explained in asymptotic terms.